2016
DOI: 10.1590/0103-8478cr20141838
|View full text |Cite
|
Sign up to set email alerts
|

pH of exudate test in the physiological quality of crambe seeds

Abstract: Crambe is a rapeseed with high oil content and can be used as a winter cover or as a source of raw material for the production of biodiesel, however espite the growing interest in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…An Acad Bras Cienc (2019) 91( 4) e20180734 8 | 10 submitted to a soaking period of 30 minutes at 25°C. In the same way that exudate -phenolphthalein pH test showed a significant correlation with the emergence of crambe seedlings, 'FMS Brilhante', in the combinations of 30 minutes at 25°C and 45 minutes at 30°C and with germination in all soaking periods tested (15, 30 and 45 minutes) at 30°C (Alves et al 2016).…”
Section: Cdm -mentioning
confidence: 54%
See 1 more Smart Citation
“…An Acad Bras Cienc (2019) 91( 4) e20180734 8 | 10 submitted to a soaking period of 30 minutes at 25°C. In the same way that exudate -phenolphthalein pH test showed a significant correlation with the emergence of crambe seedlings, 'FMS Brilhante', in the combinations of 30 minutes at 25°C and 45 minutes at 30°C and with germination in all soaking periods tested (15, 30 and 45 minutes) at 30°C (Alves et al 2016).…”
Section: Cdm -mentioning
confidence: 54%
“…The exudate -phenolphthalein pH test was efficient at 25°C for 30 minutes in the evaluation of the physiological quality of soybean seeds (G. max L.) Amaral 1986, Barros andMarcos Filho 1990). As well as, for the crambe (Crambe abyssinica Hochst) seeds, cultivar 'FMS Brilhante', in which the test was promising in the distinction of the plots at vigor levels at both the constant temperature of 25°C for 30 minutes and at 30°C for 45 minutes (Alves et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, Amaral and Peske (2000), Cabrera and Peske (2002), and Alves et al (2016) found positive correlation between the pH exudate and germination/emergence tests for wheat, corn and cramble seeds. In this way, this test is not recommended at these conditions to analyze the viability and vigor of C. limonia seeds, requiring more research about this specie to adjust the best concentration (indicator solution) and immersion periods of the seeds.…”
Section: Resultsmentioning
confidence: 97%
“…Through the data obtained by pH-measuring devices or acid-base indicator solutions, it is possible to evaluate the physiological condition of each seed and, consequently, the physiological potential of lots (Araldi and Coelho, 2015;Alves et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is a reduction in total carbohydrates, sugars, soluble and phosphate proteins, an increase in free fatty acids, destabilization of enzyme activity, and synthesis of proteins. Increase in electrical conductivity due to a decrease in the grain water content is related to the process of reorganization of cell membranes as a function of grains rehydration (Barbosa et al, 2012;Alves et al, 2016).…”
Section: Resultsmentioning
confidence: 99%